(untitled) (Bangladesh Journal of Medicine, 2016)
Worldwide occurrence of snakebite in pregnancy is little known in medical literature. Furthermore to the best of our knowledge there is no case report on Krait envenomation in pregnancy in Bangladesh. It carries significant fetal wastage and maternal morbidity and mortality. Here we report a mutligravida aged 27 years at her 24 weeks of gestation with krait bite with neuroparesis with good obstetrical outcome. Bangladesh J Medicine Jul 2016; 27(2) : 86-88